UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN GAHARU (Aquilaria malaccensis Lamk) BERDASARKAN UMUR POHON - Reza Nugraha; Ridwanti Batubara; Herawaty Ginting (Program studi Kehutanan USU, 2015)
Utilization of agarwood leaves(Aquilaria malaccensis Lamk.) suspected contain a chemical compound of the flavonoids those are flavones, flavonol and isoflavones so that the leaves used as brewed beverages which serve as antioxidant.Based on that description, researcher interested in knowing the content of chemical compounds class and test the antioxidant activity of ethanol extract of agarwood leaves (A. malaccensis Lamk.). previous research does not regard age of the tree which is taken its leaves, so that it needed to review that based on the age of the tree. This research used the trees in age 4 and 7 years after those were planted in the field. This study aims to knowing chemical compounds class that contain in agarwood leaves (A. malaccensis Lamk.) which have a function as antioxidant from the tree in age 4 and 7 years; and to knowing the power of the antioxidant activity from ethanol extract of agarwood leaves in age 4 and 7 years. This research is based on the method of Badan Ditjen POM year 1995. Based on the result of phytochemicals screening test of simplicia powder and ethanol extract of agarwood leaves which are the compounds of flavonoids, glycosides, tannins, steroid/triterpenoids, all of that are the active compounds of antioxidant. The result of antioxidant activity test using beam spectrophotometer showed in a wavelength 516 nm at 42th minutes is the result of ethanol extract of agarwood leaves in age 4 and 7 years have 27,83 ppm and 27,76 ppm of IC50. The result of this test is known that ethanol extract of agarwood leaves in age 4 and 7 years have a very strong antioxidant activity. Keywords : Agarwood leaves, Antioxidant, Phytochemicals, Age, IC50